1981
DOI: 10.1093/ajcn/34.10.2104
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sensitivities of tocopherol levels of platelets, red blood cells, and plasma for estimating vitamin E nutritional status in the rat

Abstract: The use of tocopherol levels of either platelets or red blood cells was tested as an index of tissue vitamin E status. Male Wistar rats were fed 0, 5, 10, 20, or 50 ppm of vitamin E (d-alpha-tocopheryl acetate) ad libitum for 10 wk. Over the dosage range from 0 to 20 ppm, response in tocopherol content of most tissues including platelets and red blood cells were linear. Over the whole range from 0 to 50 ppm, responses were curvilinear both directly and logarithmically for all tissues. In a comparison of reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 18 publications
4
21
0
Order By: Relevance
“…In vitro erythrocyte-to-HDL exchange of ␣-tocopherol has been described (17 ) and might contribute to the observed reduction in erythrocyte ␣-tocopherol concentrations. Although platelet tocopherol concentrations have not been demonstrated to correlate with those in peripheral nervous tissue, platelet concentrations might better reflect dietary vitamin E intake because they are not passively influenced by lipid concentrations (18 ). Our preference, therefore, was to use platelet tocopherol concentrations to assess in vivo tocopherol transport.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro erythrocyte-to-HDL exchange of ␣-tocopherol has been described (17 ) and might contribute to the observed reduction in erythrocyte ␣-tocopherol concentrations. Although platelet tocopherol concentrations have not been demonstrated to correlate with those in peripheral nervous tissue, platelet concentrations might better reflect dietary vitamin E intake because they are not passively influenced by lipid concentrations (18 ). Our preference, therefore, was to use platelet tocopherol concentrations to assess in vivo tocopherol transport.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results of the hemolysis test, the vitamin E requirement is optimally covered by the supplemented dl-Y-tocopherol whereas the equivalent amount of ¿//-a-tocopherol seems to be insufficient (table I). However, Lehmann [19] reported that an addition of only 10 mg ¿/-a-tocopherol acetate/kg diet (= 9.1 mg ¿/-a-tocopherol equivalents) is adequate to prevent several typical vitamin E deficiency symptoms. That corresponds to 1/5 of the ¿/-a-tocopherol equivalents used in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy can only be explained by the dif ferent fat components in the diets, fed to the animals of both experiments. While the semisynthetic triglyceride used in our experi ments contained only traces of unsaponifiable substances (see methods), the composi tion of the 'stripped' com oil used by Leh mann [19] is not given. We assume that it still contained available amounts of tocopherols as well as other unsaponifiable sub stances.…”
Section: Discussionmentioning
confidence: 99%
“…26 -28 In fact, beyond total vitamin E content of the whole body, tissue levels (ie, amounts of ␣-tocopherol in biomembranes) would be more meaningful than plasma levels, and the relative distribution between blood and tissues may well determine the extent of the expected beneficial outcome. 29,30 In fact, the conclusions of most human studies were built on measurements of vitamin E concentration in plasma only, and this limitation might actually account for some of the heterogeneous observations. Interestingly, arterial injury of the common carotid artery in humans was found to be negatively associated with the vitamin E content of red blood cells, but not of plasma.…”
Section: Desrumaux Et Al Pltp and Vascular Biology 2455mentioning
confidence: 99%